2022
DOI: 10.12998/wjcc.v10.i31.11646
|View full text |Cite
|
Sign up to set email alerts
|

Apnea caused by retrobulbar anesthesia: A case report

Abstract: BACKGROUND Apnea caused by retrobulbar anesthesia is a very rare but severe complication during ophthalmic surgery. CASE SUMMARY We report a rare case of apnea caused by retrobulbar anesthesia, and emergency resuscitation was used. A 74-year-old female patient was diagnosed with rhegmatogenous retinal detachment in the right eye and planned to undergo vitrectomy under retrobulbar anesthesia. After the retrobulbar anesthesia in her right eye, she became unconscious and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Hydrogels are excellent adsorbents. Wang et al 7 reported their discoveries of low-cost and highcapacity β-cyclodextrin-modified hydrogels that remove dyes, which could remove 96.58% methylene blue with an initial concentration of 400 mg/L and only require a dosage of 0.02 wt %. Afzal et al 8 synthesized chitosan/biochar hydrogel beads that adsorbed 76 mg/g ciprofloxacin within 48 h. Yan et al 9 reported Fe 3 O 4 -functionalized poly(vinyl alcohol)/chitosan hydrogels, showing admirable adsorption for Cr 6+ , about 281 mg/g.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hydrogels are excellent adsorbents. Wang et al 7 reported their discoveries of low-cost and highcapacity β-cyclodextrin-modified hydrogels that remove dyes, which could remove 96.58% methylene blue with an initial concentration of 400 mg/L and only require a dosage of 0.02 wt %. Afzal et al 8 synthesized chitosan/biochar hydrogel beads that adsorbed 76 mg/g ciprofloxacin within 48 h. Yan et al 9 reported Fe 3 O 4 -functionalized poly(vinyl alcohol)/chitosan hydrogels, showing admirable adsorption for Cr 6+ , about 281 mg/g.…”
Section: ■ Introductionmentioning
confidence: 99%